Systemic minor histocompatibility antigen expression in blood endothelial cells prevents T cell‐mediated vascular immunopathology. (6th September 2013) - Caviezel‐Firner, Sonja; Engeler, Daniel; Bolinger, Beatrice; Onder, Lucas; Scandella, Elke; Yu, Meimei; Kroczek, Richard. A.; Ludewig, Burkhard
<x xml:space="preserve">Abstract</x> Attenuation of T cell‐mediated damage of blood endothelial cells (BECs) in transplanted organs is important to prevent transplant vasculopathy (TV) and chronic rejection. Here, we assessed the importance of minor histocompatibility antigen (mHA) distribution and different coinhibitory molecules for T cell‐BEC interaction. A transgenic mHA was directed specifically to BECs using the Tie2 promoter and cellular interactions were assessed in graft‐versus‐host disease‐like and heterotopic heart transplantation settings. We found that cognate CD4+ T‐cell help was critical for the activation of BEC‐specific CD8+ T cells. However, systemic mHA expression on BECs efficiently attenuated adoptively transferred, BEC‐specific CD4+ and CD8+ T cells and hence prevented tissue damage, whereas restriction of mHA expression to heart BECs precipitated the development of TV. Importantly, the lack of the coinhibitory molecules programed death‐1 (PD‐1) and B and T lymphocyte attenuator fostered the initial activation of BEC‐specific CD4+ T cells, but did not affect development of TV. In contrast, TV was significantly augmented in the absence of PD‐1 on BEC‐specific CD8+ T cells. Taken together, these results indicate that antigen distribution in the vascular bed determines the impact of coinhibition and, as a consequence, critically impinges on T cell‐mediated vascular immunopathology.